RETRACTED: Preparing students to study in distance education - Yekimov Sergey; Vondracek Martin; Vasylyshyn Vitalii; Vasylyshyn Yaroslav; Dosbenbetova Anara; Kachailo Kseniia A.; Shekhavtsova Svitlana O. (E3S Web of Conferences)
See the retraction notice E3S Web of Conferences 420, 00001 (2023), https://doi.org/10.1051/e3sconf/202342000001